Comparison of temperature processing methods for monitoring focused ultrasound ablation in the brain. Issue 6 (4th April 2013) - Rieke, Viola; Instrella, Ron; Rosenberg, Jarrett; Grissom, William; Werner, Beat; Martin, Ernst; Pauly, Kim Butts
<x xml:space="preserve">Abstract</x> Purpose To investigate the performance of different reconstruction methods for monitoring temperature changes during transcranial magnetic resonance imaging (MRI)‐guided focused ultrasound (MRgFUS). Materials and Methods Four different temperature reconstruction methods were compared in volunteers (without heating) and patients undergoing transcranial MRgFUS: single baseline subtraction, multibaseline subtraction, hybrid single baseline/referenceless reconstruction, and hybrid multibaseline/referenceless reconstruction. Absolute temperature error and temporal temperature uncertainty of the different reconstruction methods were analyzed and compared. Results Absolute temperature errors and temporal temperature uncertainty were highest with single baseline subtraction and lowest with hybrid multibaseline/referenceless reconstruction in all areas of the brain. Pulsation of the brain and susceptibility changes from tongue motion or swallowing caused substantial temperature errors when single or multibaseline subtraction was used, which were much reduced when the referenceless component was added to the reconstruction. Conclusion Hybrid multibaseline/referenceless thermometry accurately measures temperature changes in the brain with fewer artifacts and errors due to motion than pure baseline subtraction methods. J. Magn. Reson. Imaging 2013;38:1462–1471. © 2013 Wiley Periodicals, Inc.